ANALISIS PENGARUH GAYA KEPEMIMPINAN, KOMUNIKASI DAN REMUNERASI TERHADAP MOTIVASI KERJA (Studi Cucian Motor/Mobil milik Panti Asuhan Ruth Pangkalpinang) - Surani Turnip, Tri; Ruben Manullang, Rizal; Medinal (Jurnal Progresif Manajemen Bisnis, 2018)
This undergraduate thesis was written and compiled by Tri Surani Turnip; with Student Identity Number: 230140066. It was entitled in Bahasa Indonesia: “ANALISIS PENGARUH GAYA KEPEMIMPINAN, KOMUNIKASI DAN REMUNERASI TERHADAP PENINGKATAN MOTIVASI KERJA PADA USAHA PENCUCIAN MOTOR/MOBIL MILIK PANTI ASUHAN RUTH”. The study was conducted in Pangkalpinangand implemented from March 2018 until June 2018. This study aims to determine how much influence the style of leadership, communication, and remuneration increase work motivation in the motorcycle/car wash business owned by Ruth Orphanage. This research uses quantitative analysis. The total population of this research is 54 employees and using sampling method used in this research is purposive sampling methods. Techniques of data collection use primary and secondary data. Test requirements analysis uses the test of normality, and multicollinearity test. The method of analysis used is multiple regression analysis and simple regression analysis. And hypothesis testing; t-test (partial) and F-test (simultaneous). The results of this study indicate that: (1) There is a significant influence of the variable of Leadership Style on Work Motivation in the motorcycles/car wash business that belongs to Ruth Orphanage. This is proved by the value of t-count (3.070)> t-table (2,00665). (2) There is a significant influence of the Communication variable on Work Motivation in the motorcycle/car wash business owned by Ruth Orphanage. This is evidenced by the T-count (3.057)> t-table (2,00665) (3) There is a significant effect of the Remuneration variable on Work Motivation in the motorcycles/car wash business of Ruth Orphanage. This is seen through the t-count (2,390)>ttable (2,00665), (4) There is a significant influence of variables Leadership style, Communication, and Remuneration jointly to Work Motivation on motorcycles/car wash business of Ruth Orphanage. This is proved by the value of Fhitung (4,587)> Ftable (2.79., Based on the result of the research, the researcher concludes that the Motivation of Employees of the motorcycle/car wash business which belongs to Ruth orphanage can be improved through Leadership, Communication, and Remuneration Style.